The Multifaced Politics: A Study on Polarization of Political Behavior of Tarekat Community in West Sumatera, Indonesia - Welhendri Azwar; Muliono Muliono (Al-Jami'ah Research Centre, 2022)
Tuanku as a leader of Tarekat community is a charismatic figure who plays significant socio-political roles. He is still placed as source of